Climate Governance and Decentralization in Indonesia - Gregorio, M. di; Moeliono, M. (Cambridge University Press, 2023)
Indonesia represents an interesting case for analysis of the relationship between multi-level governance and climate governance for three main reasons. It is a highly decentralized country; it is a major contributor to land-based greenhouse gas emissions; and it is extremely vulnerable to climate change. The chapter first provides a broad overview on Indonesia’s climate governance in the context of decentralization, and then focuses on sub-national governance of climate change mitigation in the land use sector, the largest contributor to greenhouse gas emissions in the country. Our research suggests that Indonesia illustrates key advantages of highly decentralized polity structures. Political autonomy has facilitated sub-national climate action through direct engagement of provinces with transnational climate initiatives, and the multiplicity of forums for policymaking has allowed certain provinces to champion sub-national engagement in climate change policy. Decentralization has also facilitated experimental policies in the form of innovative sub-national jurisdictional approaches to climate action in the land use sector. At the same time, peculiarities of the decentralization approach in the land use sector have led to perverse incentives that hamper forest-based climate change mitigation action.